Volume and effectiveness assessment of articain 4% versus mepivacaine 2% used in third molar surgery: Randomized, double-blind, split-mouth controlled clinical trial - de Almeida, Paula Carolina [UNESP]; Raldi, Fernando Vagner [UNESP]; Sato, Fábio Ricardo Loureiro [UNESP]; Nascimento, Rodrigo Dias [UNESP]; de Moraes, Michelle Bianchi [UNESP] (Medicina Oral, S.L., 2020)
Background: The different indications for extraction of the lower third molars, require resources to manage pain and discomfort, such as, for example, adequate anesthetic techniques, and the type of anesthetic used can in-fluence the management of pain in tooth extractions. Few studies in the literature compare the anesthetics 4% articaine hydrochloride and 2% mepivacaine hydrochloride showing evidence that both allow for successful pain management. This study sought to compare the volume, efficacy and safety of these two anesthetic drugs, both associated with epinephrine at a ratio of 1:100,000, used in the extraction of lower third molars. Material and Methods: A controlled, clinical, split-mouth compared these both local anesthetics in a sample of 20 patients requiring bilateral extraction of teeth. Pain was the main parameter to be assessed by means of the visual analogue scale (VAS) applied during and immediately after the surgery. Hemodynamic parameters, adverse events, presence of paresthesia and satisfaction of patients and surgeon were also analysed. Results: Pain management was more effective with mepivacaine up to two hours after surgery ( p=0.014), whereas the surgeon was more satisfied with the use of articaine during divulsion and suture ( p<0.05). However no statis-tically significant differences were found between both anesthetics regarding pain perception. Conclusions: It was observed that both anesthetics are efficient and safe in the management of pain for extraction of third molars, in which less amount of mepivacaine is needed. The satisfaction of patients and surgeon was the same for both anesthetics, with articaine being highlighted during divulsion and suture.
Keywords: Local anaesthesia; Pain; Paresthesia; Third molar